European Crisis: The Rise of Populism and Euroscepticism - Apostolovska stepanoska, Milena; Runcheva-Tasev, Hristina (Университетско издателство „Св. Климент Охридски“, 2017)
Eurosceptic and populist parties have shown strong tendencies to win power and set the political agenda for the last decades in several EU countries. The elections in some of those countries have shown that they didn’t achieve their goals, but they won signifi cant number of votes that indicates that euroscepticism and populism are not dead. The paper presents an overview of the results of some Eurosceptic and populist movements at the national elections in several EU Member States and it searches for an answer to the questions whether populism and euroscepticism are a 21st century invention, what is the ideological background of the crisis of legitimacy in the EU, how do they relate to classical political ideologies, what is the response of the mainstream politicians to these threats. The theoretical debate, which includes an overview of some of the key authors is enhanced by the author’s contribution of recommendations for the possible convincing alternatives which should be put forward to counter this phenomenon to preserve the European project.
Keywords: Euroscepticism, Populism, Ideology, European Union